2017
DOI: 10.1007/s00438-017-1307-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of differential expression genes associated with sex pheromone biosynthesis in Spodoptera exigua

Abstract: Species-specific sex pheromone is biosynthesized and released in most female moths as a chemical cue in mating communication. However, information on genes involved in this pathway is limited. The beet armyworm, Spodoptera exigua, is a cosmopolitan agricultural pest that causes severe economic losses to many crops. In China, the female sex pheromones in sex pheromone glands (PGs) of S. exigua have been measured which comprises (Z,E)-9,12-tetradecadienyl acetate, (Z)-9-tetradecen-l-ol, (Z)-9-tetradecenyl acetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 61 publications
3
26
1
Order By: Relevance
“…5) showed that FAR1 formed a clade with the identified FARs found in PGs of Helicoverpa (Hagstrom et al, 2012). FAR8 and FAR10 clustered with the Ostrinia FARs (Lassance et al, 2013), while the remaining FARs clustered with the FARs identified from the PG transcriptome data of Spodoptera (Zhang et al, 2015(Zhang et al, , 2017 and Agrotis (Gu et al, 2013;Ding and Löfstedt, 2015).…”
Section: Candidate Genes Involved In Sex Pheromone Biosynthesismentioning
confidence: 89%
“…5) showed that FAR1 formed a clade with the identified FARs found in PGs of Helicoverpa (Hagstrom et al, 2012). FAR8 and FAR10 clustered with the Ostrinia FARs (Lassance et al, 2013), while the remaining FARs clustered with the FARs identified from the PG transcriptome data of Spodoptera (Zhang et al, 2015(Zhang et al, , 2017 and Agrotis (Gu et al, 2013;Ding and Löfstedt, 2015).…”
Section: Candidate Genes Involved In Sex Pheromone Biosynthesismentioning
confidence: 89%
“…The four full-length sequences of SexiDes5 (1017 bp), SexiDes7 (1116 bp), SexiDes11 (1062 bp) and SlitDes5 (1017 bp) were obtained from the pheromone gland cDNA library transcripts (Zhang et al 2017 ) and encoded proteins with 339 aa, 372 aa, 354 aa and 339 aa, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Desaturase sequences were obtained from pheromone gland transcriptome databases for S. exigua (Zhang et al 2017 ) and S. litura (Zhang et al 2015 ). A phylogenetic tree was constructed for desaturases from S. exigua (Zhang et al 2017 ) and S. litura (Zhang et al 2015 ), based on a dataset containing 3 amino acid sequences from S. exigua , 1 amino acid sequence from S. litura and 53 amino acid sequences from other insects (Table S2 ). Evolutionary history was inferred by using the maximum likelihood method based on the JTT matrix-based model (Jones et al 1992 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Δ9-desaturases have been divided into two groups: one with a substrate chain length preference of C16 >C18 (NPVE motif), and the other with a substrate chain length preference of C18 >C16 (KPSE motif) [22]. Subsequently, the unsaturated fatty acid is subjected to chain-shortening by β-oxidation, generating sex pheromone precursors of specific chain length [23], and the carbonyl carbon is modified to form an oxygenated functional group, such as an aldehyde, alcohol, or acetate ester, and these modifications involve some key biosynthesis enzymes; fatty acyl-CoA reductase (FAR) converts these acyl chains into fatty alcohols that act as actual sex pheromone components in various moths [24][25][26], but most fatty alcohols are either oxidized into the corresponding aldehyde by dehydrogenases [27][28] or esterified to form acetate esters by acetyltransferase (ATF) [29][30][31], resulting in the final functional groups.…”
Section: Introductionmentioning
confidence: 99%